2000
DOI: 10.1177/104687810003100209
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Learning Capabilities by Providing Transparency in Business Simulators

Abstract: Prefabricated computer-based simulations usually offer a user-friendly interface. This allows inexperienced users fast access to the simulation because they do not have to possess specific knowledge about simulation techniques. Thus, giving simulation models an easy-to-use interface increases the acceptance of the simulation tool and draws attention to it. Learners are not only able to examine the results of their decisions but also the causes of these results using powerful system dynamics diagramming techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 19 publications
2
43
1
3
Order By: Relevance
“…Several studies by Größler and his colleagues [18][19][20] provided similar evidence, although some of the results were more mixed. Those, and other, studies are analyzed in [21] which, in addition to concluding that transparency is beneficial for only some learners and some learning objectives, also concluded that different methods of providing transparency (verbal explanations, videos, causal-loop diagrams, and stock and flow diagrams) are differentially effective.…”
Section: Introductionmentioning
confidence: 68%
“…Several studies by Größler and his colleagues [18][19][20] provided similar evidence, although some of the results were more mixed. Those, and other, studies are analyzed in [21] which, in addition to concluding that transparency is beneficial for only some learners and some learning objectives, also concluded that different methods of providing transparency (verbal explanations, videos, causal-loop diagrams, and stock and flow diagrams) are differentially effective.…”
Section: Introductionmentioning
confidence: 68%
“…Providing structural information about the underlying system in order to increase transparency seems to have a positive effect on performance [1][2][3]. Knowledge of cause-and-effect relationships supports learning and the development of mental models which are more similar to a real system.…”
Section: Open Accessmentioning
confidence: 99%
“…Several methods for dealing with complexity are discussed in the literature, such as in in Größler, Maier, and Milling [1], Capelo and Dias [2], Ritchie-Dunham [3], Rouwette, Größler and Vennix [4], Sengupta and Abdel-Hamid [5], Richmond [6], Sterman [7], Sweeney and Sterman [8]. However, less attention has been paid to so-called "heuristic competence" [9].…”
Section: Introductionmentioning
confidence: 99%
“…By making forecasting support systems models transparent, the users are encouraged to reflect not only on the outcomes but also on the reasons for the specific outcome. In this way individuals' and organizations' mental models are tested and the underlying model can improve (Grossler, Maier and Milling, 2000;Senge and Sterman, 1992), thus the gap between the forecasts and actual outcomes can be reduced. Furthermore, the machine learning model, built on a small set of features and supported by visualizations to support the reflection of a decision-makers, addresses important limitations of human decision-makers (Simon, 1991;Sterman, 1994and states the requirements for successful learning.…”
Section: Introductionmentioning
confidence: 99%